Fungal Aquaporins in Ectomycorrhizal Root Water Transport - Xu, Hao; Zwiazek, Janusz J. (Frontiers in Plant Science, 2020)
Ectomycorrhizal fungi influence root water transport of host plants. To delineate the exact mechanisms of how fungal partner alters root water relations, it is important to understand the functions of fungal transmembrane water channels, i.e., aquaporins, the key component in the symplastic pathways. In this paper, we discussed what roles the fungal aquaporins may play in root water transport. We also highlighted the opportunities of using integrated approaches to address rising questions in future hotspots of aquaporin and root water relations research.